Investigation of Search Heuristics in Manufacturing Optimization and Decision Support - Le, Nguyen Anh Tuan (2009)
In this high level of global competition in manufacturing industry, manufacturing firms especially in developing countries have been facing many difficulties to cope with rapidly changes of customer requirements in terms of quality and speed. One of many reasons for these firms to be suffered at the moment is their lack of advanced manufacturing technology. In this dissertation, an investigation will be carried out on search heuristics capability in finding good solution for manufacturing problem especially flowshop scheduling problem. A set of practical data of flowshop scheduling problem including processing times of a number of jobs in a number of machines has been collected from a real manufacturing company in Vietnam. By integrating search heuristic algorithms into Matlab programming software, a set of experiments which using the practical data will be examined in order to compare the efficiency of those search heuristics.